Fundamentos do serviço social na América Latina e no Caribe : os diferentes caminhos do Brasil, do Chile e de Cuba - Goin, Mariléia (2016)
The Fundamentals of Social Service in Latin America and the Caribbean are revealed as a theme permeated of concealments, because of the scarce studies published about this subject and also because of the historical-political, socioeconomic and cultural particularities of the Latin American region. In the light of the historical and dialectical materialist method, to analyze the conditions of the professional history of the Fundamentals of Social Service in Latin America and the Caribbean facing this reality "so unique and diverse" is the general objective of this thesis, in order to unveil the particularities, the conceptual approximations and disagreements, as such as the epistemological and axiological dimension which sustain the fundamentals of the profession in Brazil, Chile and in Cuba post-movement of reconceptualization. In an exploratory way, this research for joint approach used the following methodological procedures in the research process: (a) bibliographic review of materials that focus on history, theory and method of the selected countries; (b) the documentary and bibliographic research, basically in the online form, to constitute the map of analytical information sources; (c) documentary exploration and bibliographic preview (using a roadmap for guidance), to organize the information in blocks of analysis; and (d) the content analysis technique, to decode information and perform inferences with the theoretical-methodological matrix. The expositive synthesis of the results of this search allows us to conclude that the Fundamentals of Social Service in Latin America and the Caribbean, elucidate common traits in the professional genesis, but the production and reproduction of social life emanate sociopolitical particularities to countries which confer particular configuration to the profession despite of procedural and organic relationship with reality and to its concretion as professional work. These conditions — that besides historical-professional, are political, economic and social — which interpose, in the corpus of the Fundamentals, the necessary appropriation of social knowledge arrays and the movement of the national society, for designing social and political direction to the professional work, whether by conservative bias, whether emancipatory.